Nutritional status and daytime pattern of protein intake on match, post-match, rest and training days in senior professional and youth elite soccer players - Bettonviel, A. E. O.; Brinkmans, N. Y. J.; Russcher, K.; Wardenaar, F. C.; Witard, O. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
The nutritional status of elite soccer players across match, post-match, training and rest days has not been defined. Recent evidence suggests the pattern of dietary protein intake impacts the daytime turnover of muscle proteins and, as such, influences muscle recovery. We assessed the nutritional status and daytime pattern of protein intake in senior professional and elite youth soccer players and compared findings against published recommendations. Fourteen senior professional (SP) and fifteen youth elite (YP)soccer players fromtheDutch premier division completed nutritional assessments using a 24-h web-based recall method. Recall days consisted of a match, post-match, rest and training day. Daily energy intake over the 4-day period was similar between SP (2988±583 kcal/day) and YP (2938±465 kcal/day;p=0.800). Carbohydrate intake over the combined 4-day period was lower in SP (4.7±0.7 g·kg-1BM·day-1)vs.YP(6.0±1.5 g·kg-1BM·day-1,p=0.006) and SP failed to meet recommended carbohydrate intakes on match and training days. Conversely, recommended protein intakes were met for SP (1.9±0.3 g·kg-1BM·day-1) and YP (1.7±0.4 g·kg-1BM·day-1), with no differences between groups (p=0.286). Accordingly, both groups met or exceeded recommended daily protein intakes on individual match, post-match, rest and training days. A similar `balanced` daytime pattern of protein intake was observed in SP and YP. To conclude, SP increased protein intake on match and training days to a greater extent than YP, however at the expense of carbohydrate intake. The daytime distribution of protein intake for YP and SP aligned with current recommendations of a balanced protein meal pattern.